Оцінка та використання вжиткового мистецтва в контексті культурного туризму - Зафер Отер (Народна творчість та етнографія, 2010)
Today, technology is threatening the existence of handicrafts. However, handicrafts are not only an economic production activity, but convey the national memory, cultural heritage, and therefore can affect the identity on sociological, anthropological and folkloric dimension. Maintaining marketable handicrafts, especially within the scope of cultural tourism, allows preserving the intangible cultural heritage. The article studies the position of handicraft artists with regards to the tourism industry in Turkey. The author discusses the possibility to assess the handicraft through tourism products. The study followed a qualitative research method; the primary data collected in the Aegean region has been analyzed, interpreted and the findings are discussed. The author analyses the relations between cultural heritage, handicrafts and tourism, studies the marketing of handicrafts within cultural tourism. Günümüzde teknoloji el sanatlarının varlığını tehdit etmektedir. Ancak; el sanatları salt ekonomik bir üretim faaliyeti değil; ulusal hafızayı, kültür mirasını, kimliği etkileyen yönleri ile sosyolojik, antropolojik ve folklorik boyutları olan bir kavramdır. El sanatları özellikle kültür turizmi kapsamında korunarak pazarlanabilecek somut olmayan kültürel miras kapsamındadır. Bu çalışmada, Türkiye’de el sanatçılarının turizm endüstrisi ile olan ilişkileri sorgulanmaktadır. Çalışmanın temel amacı el sanatçılarının ürünlerini turizm kanalıyla değerlendirmesi için neler yapılabileceğini tartışmaktır. Çalışmada nitel araştırma yöntemi izlenerek Ege Bölgesi’nden toplanan birincil veriler analiz edilmiş, yorumlanmış ve bulguları tartışılmıştır. Çalışmada sırayla kültür mirası, el sanatı ve turizm arasındaki ilişkiler, el sanatlarının turizmde pazarlanması, kültür turizminin içeriği ve el sanatçılarına yönelik saha çalışması bölümleri yer almaktadır.